Formulation and Antimicrobial Evaluation of Bar Herbal Soap with Cinnamon Bark Powder - Neny Sandrawati; Fivit Andriani; Yuni Mala Sari; Della Rosalynna Stiadi; Anggela Marta Tasman (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Soap is an essential personal care product that not only cleanses the skin but can also provide additional health benefits, such as antibacterial protection. Cinnamon (Cinnamomum sp.) contains bioactive compounds, including flavonoids, phenolics, and cinnamaldehyde, which have demonstrated antibacterial activity. This study aims to formulate and evaluate a solid herbal soap containing cinnamon bark powder at different concentrations, and to assess its physicochemical properties and antibacterial activity against Staphylococcus aureus. The methods used include soap production via saponification of oil and an alkali base, followed by the addition of cinnamon bark powder as the active ingredient. The evaluation included organoleptic, homogeneity, pH, and foam stability tests to assess the formulation's physical and chemical quality. The antibacterial activity of the cinnamon herbal soap was tested against Staphylococcus aureus using the agar diffusion method with three replicates. The results showed that the herbal solid soap was stable and homogeneous, meeting the physical and chemical requirements for soap. The antibacterial test showed the formation of inhibition zones with diameters of 9.33 ± 0.58 mm, 10.08 ± 1.13 mm, and 11.67 ± 1.44 mm at test concentrations of 10%, 20%, and 30% w/v, respectively. These findings indicate that the cinnamon bark- based herbal soap has potential as a natural antibacterial cleansing product. Further optimization is required to enhance product quality, long-term stability, and safety.